2014
DOI: 10.3390/ijms15058998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Quaternary Ammonium Methacrylate Polymer (QAMP) on Adhesion and Antibacterial Properties of Dental Adhesives

Abstract: This study investigated the resin–dentin bond strength (μTBS), degree of conversion (DC), and antibacterial potential of an innovative adhesive system containing a quaternary ammonium methacrylate polymer (QAMP) using in situ and in vitro assays. Forty-two human third molars were flattened until the dentin was exposed and were randomly distributed into three groups of self-etching adhesive systems: Clearfil™ SE Bond containing 5% QAMP (experimental group), Clearfil™ Protect Bond (positive control) and Clearfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
1
25
0
1
Order By: Relevance
“…6,27,28 In a previous paper devoted to investigate the QAMP behaviour in dental adhesive systems, this quaternary ammonium polymer demonstrated a lower migration from the adhesive system compared to MDPB due to its high molecular weight. 6,33 Furthermore, a commercial adhesive containing QAMP (Clearfil TM SE Bond containing 5% QAMP) showed statistically similar degree of conversion than Clearfil TM Protect Bond and Clearfil TM SE Bond by in situ and in vitro analyses. 33 Thus, the main result of this paper is that QAMP incorporation did not adversely influence the exudative phase of inflammatory process which can be deeply related to the previously reported data that showed an effective lightcuring of the adhesive system containing QAMP and a low release of quaternary ammonium compounds from this dental material.…”
Section: Discussionmentioning
confidence: 81%
“…6,27,28 In a previous paper devoted to investigate the QAMP behaviour in dental adhesive systems, this quaternary ammonium polymer demonstrated a lower migration from the adhesive system compared to MDPB due to its high molecular weight. 6,33 Furthermore, a commercial adhesive containing QAMP (Clearfil TM SE Bond containing 5% QAMP) showed statistically similar degree of conversion than Clearfil TM Protect Bond and Clearfil TM SE Bond by in situ and in vitro analyses. 33 Thus, the main result of this paper is that QAMP incorporation did not adversely influence the exudative phase of inflammatory process which can be deeply related to the previously reported data that showed an effective lightcuring of the adhesive system containing QAMP and a low release of quaternary ammonium compounds from this dental material.…”
Section: Discussionmentioning
confidence: 81%
“…Generally speaking, however, with the increase of the amount of antibacterial agent, the mechanical properties and biocompatibility of the material will decrease. QACs belong to a kind of nonrelease antibacterial agent, and the antibacterial effect can be achieved when the dosage is relatively large 32,[44][45][46][47] . While the release antimicrobial agents can achieve better antibacterial effect at a low concentration, however, their extending antibacterial efficiency is low and they may be more toxic toward surrounding environments, the so-called "sudden release effect" [104][105][106][107] .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 5 wt% DMADDM was incorporated into Clearfil SE Bond by Zhang et al It had been observed that adhesives containing DMADDM inhibited the growth, lactic acid production, and Exopolysaccharides (EPS) metabolism of S. mutans biofilm at different stages, with no adverse effect on its dentin adhesive bond strength 44,45) . Besides that, Pupo et al 46,47) performed a study incorporating of quaternary ammonium methacrylate polymer (QAMP) at 5% by mass to Clearfil SE Bond as experimental group, Clearfil SE Bond as negative control group, and Clearfil Protect Bond as positive control group. The results showed that experimental group demonstrated the minimum inhibitory /bactericidal concentration (MIC/MBC) values and an inhibition zone against Lactobacillus casei (L. casei) and Actinomyces naeslundii (A. naeslundii) similar to the positive control, and higher MIC/MBC values and smaller inhibition zone than the negative control for S. mutans, L. casei, and A. naeslundii, and that no statistically significant difference in the resin-dentin bond strength (μTBS) was observed between experimental and negative control groups immediately, after 6 months, or 12 months of water storage.…”
Section: Adhesive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that these agents may reduce dentin biodegradability of host-derived MMPs, thus improving the quality of the hybrid layer. According to this review, these agents may be applied after acid-etching (27), during the priming step as modified primers (69, 70), or during the bonding step as modified resin adhesives (71, 72). …”
Section: Protease Inhibitorsmentioning
confidence: 99%